Infecção oculta pelo vírus da hepatite B em pacientes com hepatopatia acompanhados em centro de referência de Minas Gerais - Alessandra Coutinho de Faria (2016)
Long-lasting persistence of hepatitis B virus (HBV) deoxyribonucleic acid (DNA) in the liver of individuals who lack detectable hepatitis B surface antigen (HBsAg) in serum is termed occult hepatitis B virus infection (OBI). This condition may influence several clinical situations including HBV transmission by blood transfusion and organ transplantation, and endogenous viral reactivation post imunossuppression. Furthermore, OBI may contribute to the progression of other chronic liver disease, and is supposed to be a risk factor forhepatocellular carcinoma development. The prevalence and clinical importance of this condition in Brasil are not known. We undertook a study to evaluate the occurrence of OBI in patients with liver diseases. We examined 104 patients HBsAg-negative with different liver diseases, for the presence of HBV DNA by nested-polymerase chain reaction (nested-PCR) performed in liver tissue using two different previously published protocols. Fourteen patients had detectable antibodies to the HBV core antigen (anti-HBc); 47 were negative for all HBV markers. OBI was diagnosed in 6.7% of the 104 patients (considering OBI only the cases in whom HBV DNA was identified by both protocols). The first protocol identified 13 cases in the total of 104 patients and the second protocol identified nine cases. In addition to differences in the prevalence of HBV infection in different regions, variations in the PCR technique used for HBV-DNA amplification may lead to diverse sensitivity and specificity ofthe method explaining the differences in the prevalence of OBI identified in different studies. It is necessary to better standardize the method used for the diagnosis of OBI.